Porosity Characteristics of Chars Derived from Different Lignocellulosic Materials - Laila B. Khalil (Adsorption Science & Technology)
Sixteen agricultural waste products were subjected to pyrolysis at 550°C under a nitrogen atmosphere. The precursors which were treated in this manner were fruit stones and nut shells (peach, apricot and olive stones; date pits, almond, hazel nut and pistacio shells), fibrous materials (sugar cane bagasse, date palm branches and leaves, cotton stalks and wood meal), corn cobs, rice husks, alkali-washed rice hulls and barbecue charcoal. Low adsorption of nitrogen was observed at 77 K with low values being estimated for the corresponding BET surface areas and total pore volumes. The surface areas as determined from CO 2 adsorption at 303 K were relatively higher and various micropore parameters were calculated from the Dubinin–Radushkevich equation. Iodine was adsorbed from aqueous solution in amounts higher than the apparent surface areas and Methylene Blue was also taken up in a similar fashion. Such behaviour was attributed to the surface chemical natures of the chars which contribute to the higher uptake from aqueous solution. Generally, microporous products exhibiting a predominant ultramicroporosity were obtained under pyrolysis conditions.